Accumulation of 1-deoxynojirimycin in silkworm, Bombyx mori L. - Yin, Hao (Zhejiang University Press, 2010)
1-deoxynojirimycin (1-DNJ) contents in the silkworm, Bombyx mori, at different developmental stages and tissues were investigated by using reverse-phase high-performance liquid chromatography. The 1-DNJ contents of silkworm larvae change significantly with their developmental stages. The male larvae showed higher accumulation efficiency of 1-DNJ than the females and also a significant variation was observed among the silkworm strains. The present results show that tissue distribution of 1-DNJ was significantly higher in blood, digestive juice, and alimentary canal, but no 1-DNJ was observed in the silkgland. Moreover, 1-DNJ was not found in silkworms fed with artificial diet that does not contain mulberry leaf powder. This proves that silkworms obtain 1-DNJ from mulberry leaves; they could not synthesize 1-DNJ by themselves. The accumulation and excretion of 1-DNJ change periodically during the larval stage. There was no 1-DNJ in the newly-hatched larvae and 1-DNJ was mainly accumulated during the early and middle stages of every instar, while excreted at later stages of larval development. Further, it is possible to extract 1-DNJ from the larval feces and it is optimal to develop the 1-DNJ related products for diabetic auxiliary therapy.